Why Does Child Mortality Decrease With Age? Modeling the Age-Associated Decrease in Mortality Rate Using WHO Metadata From 25 Countries - Dolejs, Josef; Homolková, Helena (Frontiers in Pediatrics, 2021)
Background: Previous study analysed age trajectory of mortality (ATM) in 14 European countries, while this study aimed at investigating ATM in other continents and in countries with higher level of mortality. Data from 11 Non-European countries was used. Methods: The numbers of deaths were extracted from the WHO mortality database. Halley method was used to calculate the mortality rates in all possible calendar years and all countries combined. It enables to combine more countries and more calendar years in one hypothetical population. Results: Age trajectory of total mortality (ATTM) and also ATM due to specific groups of diseases were very similar in 11 Non-European countries and in 14 European countries. The level of mortality did not affect the main results founded in European countries. The inverse proportion was valid for ATTM in Non-European countries with two exceptions. Slower or no mortality decrease with age was detected in the first year of life, while the inverse proportion model was valid for the age range [1, 10) years in most of main chapters of ICD10. Conclusions: The decrease in child mortality with age may be explained as the result of the depletion of individuals with congenital impairment. The majority of deaths up to the age of 10 years was related to congenital impairments and the decrease of child mortality rate with age was a demonstration of population heterogeneity. The congenital impairments were latent, and may cause death even no congenital impairment was detected.